(untitled) (Pedagogical Horizons, 2022)
In the current discourse coherence is regardedas a meaningful aspect in order to meet the educational policy demand of professional teacher education. Coherent teaching-and-learning opportunities during the studies ensure the imparting of appropriate pedagogical knowledge. The focus of this article is on theoretical considerations and results of a study on the perception of coherence in teacher training. The data was collected using an online questionnaire. Initial results show a very differentiated, individual perception of content coherence by the students. A central aspect is that the coherence of the content is perceived more clearly by the students, the more consciously the teachers point it out. Overall the courses seem to be perceived as coherent.